Changes of Plantar Pressure and Gait Parameters in Children with Mild Cerebral Palsy Who Used a Customized External Strap Orthosis: A Crossover Study. (10th November 2015) - Chang, Wen-Dien; Chang, Nai-Jen; Lin, Hung-Yu; Lai, Ping-Tung
Abstract : Toe-in gait and crouch gait can make children with mild cerebral palsy fall and suffer improper balance during walking or ambulation training. A customized external strap orthosis for correcting leg alignment was used to resolve this problem. The purpose of this study was to research the immediate effects while wearing the customized external strap orthosis. Pressure platform was used to assess the plantar pressure through static and dynamic assessments and to record the changes in path of pressure trajectory. Motion image analysis system was used to record the gait parameters, which included gait speed, stride length, and cadence. The influence of both wearing and removing the orthosis on the dominant leg of children with mild cerebral palsy was analyzed. Nine children with mild cerebral palsy, who all had a dominant right leg, were recruited. After wearing the orthosis, all gait parameters improved, and foot motion changed in the stance phase of the gait cycle. The path of pressure trajectory closing to the midline was also observed during dynamic assessment. Changes in plantar pressure and path of pressure trajectory were observed and the orthosis device could provide immediate assistance to correct the leg alignment and improve the gait performance in children with mild cerebral palsy.